Political regime and COVID 19 death rate: Efficient, biasing or simply different autocracies?An econometric analysis. - Guilhem Cassan; Milan Van Steenvoort (Elsevier, 2021)
The difference in COVID 19 death rates across political regimes has caught a lot of attention. The "efficient autocracy" view suggests that autocracies may be more efficient at putting in place policies that contain COVID 19 spread. On the other hand, the "biasing autocracy" view underlines that autocracies may be under reporting their COVID 19 data. We use fixed effect panel regression methods to discriminate between the two sides of the debate. Our results present a more nuanced picture: once pre-determined characteristics of countries are accounted for, COVID 19 death rates equalize across political regimes during the first months of the pandemic, but remain largely different a year into the pandemic. This emphasizes that early differences across political regimes were mainly due to omitted variable bias, whereas later differences are likely due to data manipulation by autocracies. A year into the pandemic, we estimate that this data manipulation may have hidden approximately 400,000 deaths worldwide.